2010
DOI: 10.1038/jid.2010.46
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Generalized Non-Herlitz Junctional Epidermolysis Bullosa

Abstract: Epidermolysis bullosa (EB) is a class of intractable, rare, genetic disorders characterized by fragile skin and blister formation as a result of dermal-epidermal mechanical instability. EB presents with considerable clinical and molecular heterogeneity. Viable animal models of junctional epidermolysis bullosa (JEB), that both mimic the human disease and survive beyond the neonatal period, are needed. We identified a spontaneous, autosomal recessive mutation (Lamc2 jeb) due to a Murine Leukemia Virus long termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 53 publications
(58 reference statements)
1
39
0
Order By: Relevance
“…Specifically, fibroblast based cell therapies of collagen VII deficient dystrophic epidermolysis bullosa demonstrated that about 35% of physiological levels of the collagen confer greatly improved skin integrity9 10 and, in a human pilot trial, gene therapy for JEB partially restored laminin 332 in the skin and significantly ameliorated the phenotype 11. This was corroborated by a recently described laminin gamma-2 hypomorphic mouse,12 which has low levels of laminin 332 in the skin and a moderate phenotype, in contrast to the perinatally lethal laminin 332 knockout mice 13–15. These observations suggest that the multiprotein complexes at the dermal–epidermal junction are highly stable with robust interactions of the binding partners, which can compensate a significant, but not complete, loss of one component.…”
Section: Introductionmentioning
confidence: 73%
“…Specifically, fibroblast based cell therapies of collagen VII deficient dystrophic epidermolysis bullosa demonstrated that about 35% of physiological levels of the collagen confer greatly improved skin integrity9 10 and, in a human pilot trial, gene therapy for JEB partially restored laminin 332 in the skin and significantly ameliorated the phenotype 11. This was corroborated by a recently described laminin gamma-2 hypomorphic mouse,12 which has low levels of laminin 332 in the skin and a moderate phenotype, in contrast to the perinatally lethal laminin 332 knockout mice 13–15. These observations suggest that the multiprotein complexes at the dermal–epidermal junction are highly stable with robust interactions of the binding partners, which can compensate a significant, but not complete, loss of one component.…”
Section: Introductionmentioning
confidence: 73%
“…Mus pahari skin consistently separated at a low force, typically 7–12 Newtons, with no apparent age or sex difference (Figure 3a,b). For comparison, B6.129X1- Lamc2 jeb/jeb /Dcr, mutant mice with non-Herlitz junctional epidermolysis bullosa, 12 week old female skin was removed at 19–23 Newtons (Bubier et al, 2010; Sproule et al, 2014; Sproule et al, 2012). Histologic evaluation of the tails that required a great deal of tension, often without success, had normal attachment of the epidermis and dermis.…”
Section: Resultsmentioning
confidence: 99%
“…This aspect of the strain’s phenotype has been incidentally noted, although there was no mention of excessively fragile skin in the original phenotypic description of this species by Thomas. Fragile (tail) skin is also a feature of a spontaneous non-Hertlitz junctional epidermolysis bullosa mouse model also discovered at The Jackson Laboratory (Bubier et al, 2010). A comparative evaluation of the skin fragility in M. pahari mice is presented here to define the underlying cause.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, long-term effects of therapeutic approaches cannot be evaluated in these models (Mühle et al, 2006). There is one mouse strain with a hypomorphic mutation of LAMC2 resulting in non-Herlitz JEB in homozygous animals (Bubier et al, 2010); however, LAMC2 mutations cause only a minority of human JEB cases (Schneider et al, 2007). A mouse model with a defective LAMB3 gene that would be suitable for evaluating novel treatments is still missing.…”
mentioning
confidence: 98%